Analysis of Incentives, Leadership and Work Environment in Improving Employee Performance - Hendi Chandra; Astri Ayu Purwati; Mazzlida Mat Deli (Yayasan Pendidikan Islam Al-Matani, 2023)
This study aims to determine the effect of incentives, leadership and work environment to employees performance in PT. Yanmarindo Perkasa. This analysis is based on 80 respondents, this study uses methods nonprobability sampling with Random sampling method and were collected through questionnaires. And research shows that the performance of employees on incentives, leadership and working environment in the process and in tests using test validity and reliability, and classical assumption that generate influence on employee performance. This research is expected that the company could maintain and improve incentives, leadership and work environment so that the employee's performance can be maintained.